"Like I always knew it": The phenomenology of intergenerational transmission of trauma in three generations of Armenian women in Turkey - Marazyan, Janin (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
"Hep biliyormuşum gibi": Türkiye'deki üç kuşak Ermeni kadınlarında tramvanın kuşaklararası aktarım fenemonojisi